INFLUENCE OF 24-HOUR BLOOD PRESSURE PATTERNS ON STRUCTURAL AND FUNCTIONAL CHANGES OF THE HEART IN PATIENTS WITH RESISTANT ARTERIAL HYPERTENSION - V. A. Lichikaki; S. E. Pekarsky; V. R. Mordovin; R. S. Karpov (Российский кардиологический журнал)
Aim. To study the relationship of 24-hour BP patterns in patients with AH resistant to drug treatment and structural-functional changes in heart before and after sympathetic denervation of the kidneys.Material and methods. The study included 53 patients (25 women and 28 men) with a diagnosis of II stage hypertension, resistant to drug therapy. Mean quantity of continuous drug compounds taking is 4,09±1,16. baseline office SBP for all patients — 176,3±19,9 mmHg, by ABPM — 158,2±14,5 mmHg, left ventricle myocardium mass (LVMM) — 275,3±91,9 g. All patients under the informed consent conditions underwent renal denervation with endovascular catheter. We analyzed the data from 46 patients (87%), studied in 6 months after ablation. All patients before and after the procedure underwent 24-hour BP monitoring and echocardiography Results. Depending on the grade of hypotensive effect after denervation all patients were divided into groups of responders (35 persons), non-responders (11 patients). In responders we found higher level of office SBP and DBP at baseline as variability of BP. In 6 months after ablation variability of SBP and DBP, level of mean daily SBP and DBP, and office values of SBP and DBP were significantly higher than in non-responders. Comparing ABPM parameters with the patterns of echocardiographic changes of the heart there were no significant differences between the groups of responders and non-responders.Conclusion. The data obtained makes evident that the decrease of hypertrophy of the left ventricle in the patients with resistant AH by sympathetic renal denervation is predefined at first by a grade of mean daily levels of BP by the data of 24-hour monitoring and also significantly by the dynamics of 24-hour BP index.